The long and winding road towards fiscal decentralization - Alzua, Maria Laura (2014)
This paper offers a theoretical explanation of the difficulties embodied in a process of fiscal decentralization from national to sub-national governments, as it is empirically observed in numerous developing countries. A game theoretic framework is used to show that the central government’s lack of a credible commitment technology, used to penalize sub-national governments’ fiscal profligacy, may give rise to an incomplete level of fiscal decentralization. Two different sets of equilibria are obtained. In one of them the central government will confer complete taxing autonomy to the subnational governments, while in the other the government maintains the taxing authority since it is optimal to do so. In this case, the economy falls in an inefficient level of fiscal decentralization, as measured in terms of revenue collection.